Selección y contratación del personal del Gobierno Autónomo Descentralizado del Cantón Baba - Cadena Ramírez, Patricia Jaqueline (2019)
The research was carried out in the Decentralized Autonomous Government of the city of Baba, an institution of public law that has administrative autonomy for the search of the integral development of the rural and urban population of the sector; The objective of the work is to determine how an inadequate process of recruitment and recruitment of personnel in relation to the functions performed by the GAD affects. The methodology conformed by the type of descriptive research, the inductive and deductive method was applied, together with the survey technique and instrument (questionnaire) for data collection. The results show that there is no human team with adequate work profile, poor labor productivity and a regular procedure is not used in the calls